PENGARUH MOTIVASI BERPRESTASI DAN EFIKASI DIRI TERHADAP KOMITMEN BERWIRAUSAHA SERTA DAMPAKNYA PADA KINERJA USAHA (Suatu Survai pada Wirausahawan Rumput Laut Skala Kecil di Provinsi Sulawesi Selatan) - Romansyah Sahabudin (Indonesian Journal of Economics and Business, 2011)
The purpose of this study was to obtain empirical evidence and find clarity about the phenomenon of the influence of achievement motivation and self-efficacy toward the entrepreneurial commitment of seaweed entrepreneurs and its impact on business performance of small-scale seaweed enterprise in South Sulawesi Province.The method used is survey research with data collection techniques using questionnaires to determine the small-scale seaweed entrepreneurs’ assessment to the variables studied. The type of research is descriptive-verification.Sample size of 387 respondents drawn through proportional cluster random sampling technique from the targeted population of 11 370 small-scale seaweed entrepreneurs spread over ten districts of South Sulawesi province.To test the hypothesis proposed, structural equation modeling (SEM) is used as a model framework that is composed through the measurement model and structural model of causal relationships among variables. The implication of this study is that the entrepreneurial commitment has contributed a more dominant influence of achievement motivation and self efficacy on the business performance, either directly or indirectly through a entrepreneurial commitment.